ANUPAMA – Torch Bearer for New Generation Women in Sudha Murty’s Mahashweta - Ms. Kajal Paghdal (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The literature of India has played a significant part in the growth of both India and the rest of the globe. One of the most influential Indian women authors, particularly Sudha Murty, is an example of this. The writings of Sudha Murty are regarded as landmarks in contemporary English literature. As a prolific writer, she is able to cover a wide range of topics in her critique of society, including the political, social, educational, and home lives of Indian women. The purpose of the paper is to study the evolution of a new woman in Sudha Murty’s novel Mahashweta. Women started regaining their lost identity and position in the last few decades of twentieth century, it was majorly due to the efforts laid by social reformers and the writers who penned down the importance of equality. The paper will highlight the difficulties faced by the protagonist as the replica of most of the women in male dominated society. At last with her education, she is able to follow her dream and live a successful life without any support of man in her life.